Optimization and purification of α-glucosidase inhibitor from Bacillus subtilis yt20 isolated in Vietnam - Nguyen, Tien Cuonh; Le, Thanh Hoang; Mai, Van Hien; Hoang, Thi Yen; Nguyen, Thi Trung; Dao, Thi Mai Anh; Nguyen, Manh Cuong; Tuyen, Do Thi (Vietnam Journal of Science and Technology, 2021)
Among the treatments of type 2 diabetes, the α-glucosidase inhibitor has been drawing the researcher’s interest world-wide because of safe and convenient mechanism. However, recent α-glucosidase inhibitors have side effects, so alternative sources have been studied to limit the side effects and provide more options for the treatment of type 2 diabetes. In this study, after selecting morioorganism strains capable of biosynthesis of α-glucosidase inhibitor from the collection of Bacillus subtilis, we have isolated B. subtilis YT20 which inhibited α-glucosidase above 90%. In detail, this number increased multiply by 1.4 times after the optimization of culture conditions. The α-glucosidase inhibitor activity of  B. subtilis YT20 yield the molecular weight of 163 Da after purified by a combination of salting out, filter membrane with pore size 1000 Da and 100 Da respectively, activated charcoal and chromatography column Sephadex G100, the efficiency peak at 16%. The spectral data indicated that the putative compound isolated from B. subtilis YT20 was 1-deoxynojirimicin. In the thin layer chromatography result, there was an appearance of a single band which corresponds to standard 1-deoxynojirimicin (Sigma), followed by a retention factor of 0.34 with a solvent system of isopropanol: acetic acid: deionized water (4:1:1).